Traumatic fractures in adults: missed diagnosis on plain radiographs in the Emergency Department - Pinto, Antonio; Berritto, Daniela; Russo, Anna; Riccitiello, Federica; Caruso, Martina; Belfiore, Maria Paola; Papapietro, Vito Roberto; Carotti, Marina; Pinto, Fabio; Giovagnoni, Andrea; Romano, Luigia; Grassi, Roberto (Acta Biomedica Atenei Parmensis, 2018)
Radiography remains the imaging standard for fracture detection after trauma. The radiographic diagnosis of most fractures and dislocations poses little difficulty to radiologists: however, occasionally these injuries are quite subtle or even impossible to detect on radiographs. Missed diagnoses of fracture potentially have important consequences for patients, clinicians, and radiologists. Radiologists play a pivot role in the diagnostic assessment of the trauma patients: emergency radiologists who are more practiced at seeking out and discerning traumatic fractures can provide an invaluable service to their clinical colleagues by ensuring that patients do not endure delayed diagnoses. This is a narrative review article aims to highlight the spectrum of fractures in adults potentially missed on plain radiographs, the causes of error in diagnosis of fractures in the emergency setting and the key elements to reduce misdiagnosis of fractures.